2022
DOI: 10.3390/molecules27154925
|View full text |Cite
|
Sign up to set email alerts
|

MXenes Thin Films: From Fabrication to Their Applications

Abstract: Two-dimensional MXenes possessed exceptional physiochemical properties such as high electrical conductivity (20,000 Scm−1), flexibility, mechanical strength (570 MPa), and hydrophilic surface functionalities that have been widely explored for energy storage, sensing, and catalysis applications. Recently, the fabrication of MXenes thin films has attracted significant attention toward electronic devices and sensor applications. This review summarizes the exciting features of MXene thin film fabrication methods s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 179 publications
0
10
0
Order By: Relevance
“…The highly preferred way in laboratory conditions for processing the MXene solutions to form a film is the filtration methods such as vacuum- and pressure-assisted filtration methods. In vacuum-assisted filtration methods, the MXene dispersion is filtered through a porous filter substrate under vacuum to form a free-standing MXene layer . Film thickness can be adjusted by varying the concentration of MXene in dispersion and filtration volume.…”
Section: Introductionmentioning
confidence: 99%
“…The highly preferred way in laboratory conditions for processing the MXene solutions to form a film is the filtration methods such as vacuum- and pressure-assisted filtration methods. In vacuum-assisted filtration methods, the MXene dispersion is filtered through a porous filter substrate under vacuum to form a free-standing MXene layer . Film thickness can be adjusted by varying the concentration of MXene in dispersion and filtration volume.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that Ti 3 CNT x is less stable than Ti 3 C 2 T x , and the stability is even worse when fabricated as a thin film . It is known that MXene thin films degrade when exposed to a humid environment, which hampers many of their potential applications . Thus, we tested the environmental stability of Ti 3 CNT x thin films with an increased number of spin-coating cycles.…”
Section: Resultsmentioning
confidence: 99%
“…MXenes are a large family of 2D materials consisting of transition metal carbides, nitrides, and carbonitrides, first described in 2011 . MXene films exhibit high conductivity (>20000 S cm –1 according to some reports), hydrophilicity, and excellent water dispersibility, and robust photon absorption in a wide wavelength range . To date, Ti 3 C 2 T x MXene has received more attention than other MXenes due to its ease of fabrication, excellent electrochemical performance, tunable optical properties, and fair stability. , Solid solution MXenes, such as Ti 3 CNT x , are also starting to gain attention due to their intriguing physical properties .…”
Section: Introductionmentioning
confidence: 99%
“…Filtration is a self-limiting process, meaning that the film on the filter membrane will naturally become uniform and dense through van der Waals forces. 118 Subsequently, the thick MXene layer must be carefully detached from the filter membranes and can eventually be employed in various applications. The elements that influence film formation include the filter membrane type, the suction speed, the solvent used, and the concentration of MXene.…”
Section: Literature Reviewmentioning
confidence: 99%